Vanuatu Gender and Investment Climate Reform Assessment - Hedditch, Sonali; Manuel, Clare (International Finance Corporation, Washington, DC, 2017)
This report is one of six gender and investment climate reform assessments undertaken in six Pacific nations including Vanuatu. The report analyses gender-based investment climate barriers which constrain private sector development and identifies solutions to address them. Four investment climate areas are considered: public private dialogue; starting and licensing a business; access to justice, the courts, and mediation, and; access to and enforcement of, rights over registered land. In each area the report considers legal, regulatory, and administrative barriers to private sector development with a gender perspective. It makes recommendations aimed at ensuring that women benefit from ongoing efforts to improve Vanuatu’s investment climate on the same basis as their male counterparts. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.